PEMBERSIH UDARA BUANG PADA BOILER (KETEL) UAP DENGAN MENGGUNAKAN ELECTROSTATIC PRECIPITATOR (ESP) PADA PLTU ASAM-ASAM - Syarifil Anwar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
Asam-asam Steam Power (power plant) is the powerhouse that has an installed capacity of 260Mw (4x65Mw) which is expected to meet the requirement of power supply in the region of South Kalimantan and Central Kalimantan. In keeping operations of the entire electricity power generation equipment can run smoothly and well, it must be held maintenance (Maintenance) and monitoring good and accurate. Steam Power (power plant) which works continuously for 24 hours each day using coal fuel. Power Plant works / operates based on certain hot steam generated by the boiler which is working with a combustion boiler water in the boiler using coal powder fuels, which would certainly lead to the air in the boiler being dirty form of coal dust. So that exhaust air from the boiler flue into space is not dirty, then we need a sucker (Wash) coal dust by using Electrostatic Precipitator (ESP) Keywords: Boiler, Combustion System boiler, dust coal fuel, Operations elecrostatic Precipitator (ESP)